Tax Knowledge and Service Quality to Motor Vehicle Taxpayer Compliance - Mario Fransisco Adikur; Ahmad Fadhil Imran (Jurnal Akuntansi, 2022)
There are so many people who have vehicles that are not aware of the benefits and importance of taxpayer compliance. This problem is marked by the increasing number of motorized vehicles every year, but not in tandem with the number of taxpayers' vehicles re-registering and paying taxes at the SAMSAT office. After being identified, the reasons were partly because public knowledge about tax regulations and procedures was deemed not optimal and the quality of service seemed unsatisfactory for some people. To ensure that, this research is here with the aim of revealing the public perception of taxpayers. Reviewing the extent of their knowledge of taxation and their level of satisfaction with the quality of services provided. This effort brings us to the question: whether tax knowledge and service quality can affect taxpayer compliance or not. This type of research is a case study with a quantitative approach. The population taken is the taxpayer of two-wheeled motorized vehicles registered in SAMSAT DIY. By using convenience sampling technique, we determine a sample of 102 people who come from two-wheeled motorized vehicle taxpayers as respondents who will fill out the questionnaire. Data were analyzed using descriptive statistics, multiple linear regression, F-test, and coefficient of determination. The results of this study indicate that the variables of tax knowledge and service quality are proven to affect taxpayer compliance in paying for two-wheeled motorized vehicles.